Deskripsi Respon Imun Non Spesifik Kakap Putih (Lates calcarifer) yang Diberi Jintan Hitam (Nigella Sativa) Dan Uji Tantang Dengan Viral Nervous Necrosis - Sonida, Aulia; Harpeni, Esti; Tarsim, Tarsim (AQUASAINS, 2014)
Asian seabass (Lates calcarifer) is one of the fish has a high economic value and widely cultivated in Indonesia. However, Asian seabass cultured constrains by infectious diseases such as Viral Nervous Necrosis (VNN). Application of antibiotics during cultured cause resistance and residues in the body of fish. Disease prevention method by use immunostimulant develop to enhances non-specific responses. The purposes of this research were to know the best dose of black cumin (Nigella sativa) that can increase the non-specific immune response of Asian seabass after injected by VNN. This research used four treatments (0 g black cumin/kg of feed, 25 g black cumin /kg of feed, 50 g black cumin/kg of feed and 75 g black cumin/kg of feed). Total leucocyte and differential leucocyte analyzed descriptively. The results showed that dose of 75 g black cumin/kg of feed is the best Â for increase the non-specific immune response of Asian seabass which had been seen from the highest total leucocyte. However, there was no effect of administrated of black cumin to Asian seabass after injected with VNN which had been seen from the RPS.